Recycling construction and demolition waste: A case study in the Euphrates Basin area in the eastern region of Syria - Shamiah, Moslem J.; Madlaji, Maad S.; Nassour, Abdullah G. (Kuwait Journal of Science, 2018)
This paper investigates using recycling and demolition waste from the Euphrates Basin in eastern Syria as concrete aggregate. The recycled aggregate samples were tested in comparison to natural river ones. Samples from governmental buildings and normal housing units (including lean concrete, white and black brick, and mixed brick with ceramic) were selected and tested individually in order to determine their properties. Normal Portland cement was used (350 kg/m3, watercement ratio 0.5 and tap water). The recycled building material was ground into various combinations of coarse and fine recycled aggregates. Natural aggregates were also used for comparison. The concrete was casted into cubes for up to 28 days and monitored under continuous curing in tap water. The cube compressive strength of the concrete made from recycled aggregate types ranged from 24 to 30 MPa. Comparing natural and recycled aggregate values showed similar results, except for the sample obtained from reinforced concrete taken from normal housing buildings, where the cube compressive strength value exceeded 6%. The compressive strength of concrete that made from other recycled aggregate types reached 90% of the natural one, which was 28.49 MPa in the natural samples. In addition, abrasion test values varied between 29.55% to 44.36%. Results showed that recycled concrete aggregates produced from construction and demolition waste in Euphrates Basin, Syria can be used in concrete works.